Training and Field of Scriptwriters in Chile:Qualitative Analysis from Interviews; [Formação E Atuação Dos Roteiristas No Chile: Análise Qualitativa a Partir de Entrevistas]; [Formación y Campo de Los Guionistas en Chile: Análisis Cualitativo a Partir de Entrevistas] - Dittus-Benavente, R (Pontificia Universidad Catolica de Chile, 2024)
The article is part of a larger study to describe the teaching of audiovisual scriptwriting and the training of scriptwriters in contemporary Chile. The results come from the application of the semi-structured interview method to ten renowned national scriptwriters and teachers in the field, verifying the existence of aesthetic orientations, technical requirements, relationships with other agents in the field or ways of working for creative writing in the stage pre-production for film and television. Open-ended questionnaires were used, the aim of which was to generate the replica of a conversation from certain predefined thematic nuclei. Based on these generative nuclei, the interviews were developed in a flexible manner, with the aim of reinforcing the non-standardized nature of the instrument. What is presented in this synthesis are common points and other controversial aspects. They have no statistical value, but rather show the importance of the complexity of the generated discourses. © 2024 Pontificia Universidad Catolica de Chile. All rights reserved.
Keywords: script; cinema; television; Chile; audiovisual industry; scriptwriter